Towards a Caribbean economy in the twenty-first century : essays in honour of William Gilbert Demas - Clarke, Laurence ed. (Caribbean Centre for Monetary Studies St. AugustineTT, 1997)
Comments on Demas : the man. Deals with technical aspects of the principle focus of Demas' lifework viz. economic development of small states and regional integration. Assesses the current state of development in the region and offers some possible solutions for the future. Looks at the way forward and comments on Demas' recent reflections on current issues in Caribbean development.